2010
DOI: 10.1007/978-3-642-14515-5_111
|View full text |Cite
|
Sign up to set email alerts
|

PDMS Anatomical Realistic Models for Hemodynamic Studies Using Rapid Prototyping Technology

Abstract: Abstracts ABOUT 6 th WORLD CONGRESS OF BIOMECHANICSThe 6th World Congress of 8iomechanics is hosted by 8iomedical Engineering ~ociety of Singapore (8ES) together with the Global Enterprise for Micromechanics and Molecular Medicine (GEM4) and the National University of Singapore (NUS), in conjunction with the 14th International Conference on 8iomechanical Engineering (lC8ME) and the 5th Asian Pacific Conference on 8iomechanics (AP8iomech). With over 2,000 delegates from ali over the World, especially from the A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…However, even performing these studies in animal models, neither human physiology nor human disease is fully recapitulated. In these types of experiments, the measurements are often inaccurate, and the experiments are expensive, have low reproducibility, and have associated ethical issues [3][4][5][6]. Therefore, engineered in vitro biomodels have gained widespread attention and have been developed to overcome those limitations.…”
Section: Introductionmentioning
confidence: 99%
“…However, even performing these studies in animal models, neither human physiology nor human disease is fully recapitulated. In these types of experiments, the measurements are often inaccurate, and the experiments are expensive, have low reproducibility, and have associated ethical issues [3][4][5][6]. Therefore, engineered in vitro biomodels have gained widespread attention and have been developed to overcome those limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Goudot et al [32] showed the ability of ultrafast ultrasound imaging to evaluate local flow velocities over an entire 2D image, which allowed the obtention of accurate measurements of wall shear stress (WSS) when compared to conventional ultrasound imaging. Although research has progressed to overcome the difficulties of in vivo measurements, these methods are still expensive, have low reproducibility, and require ethical and regulatory considerations [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…These materials are characterized by the high deformations that they exhibit before reaching the tensile strength [2]. In order to find a material with hyperelastic properties close to arterial tissues, aneurysms in vitro models made of polydimethylsiloxane (PDMS) are gaining popularity among the biomedical research community [6][7][8][9]. PDMS is a biomaterial known for its biocompatibility and low cost, which makes this material extremely popular in several biomedical applications, such as the development of biomedical microfluidic devices and organs-on-a-chip platforms [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%